Islamic Religious Counselor in Religious Social Guidance For The Elderly - Safitri, Ivani Puji; Subhi, Muh.Rifai; Rahman, Siti Fatinnah Binti Ab.; Sholeh, Muh Ibnu (Al Irsyad: Jurnal Studi Islam, 2024)
Studies on the structured process of Islamic religious counseling for the socio-religious development of the elderly remain limited, particularly regarding counseling mechanisms and social interactions within routine preaching activities. This study examines the role of Islamic religious counselors in supporting the spiritual and social development of the elderly to become more independent, spiritually active, and mentally healthy. Using a qualitative descriptive method, this field research collected data through interviews, observations, and analysis to conclude. The findings reveal that Islamic religious counseling at Majelis Ta’lim An-Nisa is conducted in a structured and systematic manner, with the strategic role of the ustadz who integrates the dakwah methods of Bil-Hikmah and Mauizhatul-Hasanah. This approach effectively enhances the spirituality and mental health of the elderly. Additionally, elderly motivation, positive social interactions, and engaging preaching methods are key factors supporting the success of socio-religious development in the elderly, which have been underexplored in previous research on religious counseling for seniors. In conclusion, religious counseling for the elderly includes sholawat, dzikir, sermons, pilgrimages, and the strengthening of spirituality and social interactions within the religious community.